GCMS-based profiling revealed bioactive compounds from Aquilaria malaccensis leaf extract - Zainurin, Nur Aimi Aliah; Hashim, Yumi Zuhanis Has-Yun; Mohamed Azmin, Nor Fadhillah; Al-Khatib, Ma'an Fahmi Rashid (2019)
Bioactive compounds from plants have been shown to possess therapeutic values which are being used as medicine as well as ingredients for functional foods and nutraceuticals. While qualitative and quantitative studies on the bioactive compounds of plant extract are important to establish their claimed therapeutic properties; less is focused on effects and interrelationship of process (extraction) conditions used to obtain the desired bioactive compounds. As such, this study intends to determine the effects of different parameters on the extraction of Aquilaria malaccensis leaf extract (ALEX) bioactive compounds. Metabolite profiling of bioactive compounds of ALEX samples were conducted using gas chromatography-mass spectrometry (GCMS) with subsequent multivariate statistical analysis through principal component analysis (PCA) with the aid of MATLAB software. The GCMS analysis detected diverse potential bioactive compounds in ALEX samples with hydrocarbon, terpenes and esters being the primary groups. n-hexadecanoic acid and hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester were found to be present in most of the ALEX samples. PCA showed that same Soxhlet extraction parameters were able to cluster the samples together and separate samples extracted with different extraction parameters based on the relative abundance of the particular compounds. In conclusion, it is notable that the samples were significantly separated based on Soxhlet extraction time as compared to the solid to solvent ratio.The findings from this study would facilitate in extraction and purification of the desired bioactive compounds from agarwood leaf that could be further used in development of functional foods and nutraceuticals.